Rigid internal fixation with titanium versus bioresorbable miniplates in the repair of mandibular fractures in rabbits - Hochuli-Vieira, Eduardo [UNESP]; Cabrini Gabrielli, M. A. [UNESP]; Pereira-Filho, V. A. [UNESP]; Gabrielli, Mário Francisco Real [UNESP]; Padilha, J. G. [UNESP] (Elsevier, 2005)
The purpose of this study was to compare by qualitative histology the efficacy of rigid internal fixation with titanium system and the Lacto Sorb® system in mandibular fractures in rabbits. Thirty male adult rabbits Oryctolagus cuniculus were used. Unilateral mandibular osteotomies were performed between the canine and first premolar. The animals were divided into two groups: for Group I - rigid internal fixation was performed with titanium system 1.5 mm (Synthes, Oberdorf, Switzerland), with two screws of 6 mm (bicortical) on each side of the osteotomy. For Group II-rigid internal fixation was performed with PLLA/PGA system 1.5 mm (Lacto Sorb®, WLorenz, Jacksonville, FL, USA). The histological analysis evaluated the presence of inflammatory reaction, degree of bone healing and degree of resorption of the Lacto Sorb® screws. The results of both fixation systems were similar, only with a small difference after 15 and 30 days. In Group I a faster bony healing was noted. But after 60 days, bony healing was similar in both groups. It is concluded that both PLLA/PGA and titanium plates and screws provide sufficient strength to permit mandibular bone healing. The resorption process of PLLA/PGA osteosynthesis material did not cause acute or chronic inflammatory reaction or foreign body reaction during the studied period. © 2004 International Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Bioresorbable plates; Bony healing; Mandibular fracture; polyglactin; polyglycolic acid; titanium; animal experiment; animal model; animal tissue; bone plate; bone screw; canine tooth; chronic inflammation; comparative study; controlled study; foreign body reaction; fracture healing; histopathology; inflammation; male; mandible fracture; mandible osteotomy; nonhuman; osteosynthesis; osteosynthesis material; premolar tooth; qualitative analysis; rabbit; strength; Absorbable Implants; Animals; Biocompatible Materials; Bone Plates; Bone Screws; Equipment Design; Fracture Fixation, Internal; Giant Cells; Lactic Acid; Male; Mandibular Fractures; Osteoblasts; Osteocytes; Osteogenesis; Osteotomy; Polyglycolic Acid; Polymers; Rabbits; Time Factors; Titanium; Wound Healing